Sentences types and pragmatic function of directive speech acts in motivational text of Atomic Habits - Devi Rosmawati; Aris Munandar; Ni Gusti Ayu Roselani (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
Directive speech acts are commonly used to influence behavior, but they are not always expressed through direct commands. In many contexts, directive meanings are conveyed indirectly through declarative or interrogative structures, requiring interpretation based on context. This indirectness is particularly characteristic of motivational discourse, where authors seek to encourage behavioral change while maintaining a persuasive and non-authoritative tone. Rather than issuing explicit instructions, motivational texts often guide readers through explanations, evaluative statements, and reflective questions. This study investigates the realization of directive speech acts in Atomic Habits by James Clear. Drawing on John Searle’s speech act theory, the analysis focuses on sentence types, modes of realization (explicit and implicit), and pragmatic functions. The data consist of 525 sentences or clauses identified as conveying directive meaning, analyzed using qualitative pragmatic interpretation and descriptive quantitative methods. The findings show that directive speech acts are predominantly realized through declarative forms, followed by imperative and interrogative structures. Indirect (implicit) directives occur more frequently than direct (explicit) ones, indicating the importance of subtle persuasive strategies in motivational writing. Pragmatically, these directives mainly function to advise, instruct, and invite reader reflection. This study contributes to pragmatic and discourse studies by demonstrating how motivational texts systematically employ indirect directive strategies to promote voluntary behavioral change. It also provides a more nuanced understanding of how directive force operates beyond imperative forms, particularly in persuasive self-improvement discourse.